(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The provision and quality of bedding materials affect the behaviour, welfare, and health of dairy cows. This paper present the experimental study of CDA and RHA as partial replacement of ordinary portland cement in M:15 mix proportional ratio 1:2:4 is used and tested for consistency limit ,setting time, workability of CDA and RHA with ordinary portland cement .cement was replace with CDA and RHA by weight of 5%,10%,15%,20%,25% respectively in concrete.